Emil Utitz et la « science générale de l’art » - Lara Bonneau (Recherches Germaniques)
This article is a contribution to the genealogy of the Science of Art, a discipline that emerged in the German speaking countries at the turn of the 19th and 20th centuries at the crossing of aesthetics, art philosophy and art history and to which the Second World War brought an end. It attempts to revive a relatively unknown figure: the German-speaking Czech philosopher Emil Utitz (1883-1956), who in the 1920s and 1930s tried to give a philosophical grounding to this new science. Against what he regarded as an aesthetic subjectivism—be it the aesthetics of the judgement of taste, the Hegelian science of beauty or the psychophysiological aesthetics—Utitz developped an ontology of the work of art based on its “objectality”. The article attempts to retrace the key elements of this systematisation project.